Effective VAR management and its impact on refereeing governance: A study of Kurdistan region fans in the Iraq Stars League - Sulaiman, Sarkaft Rashed; Zeebaree, Mohammed R. Yaseen; Ramadhan, Bewar Mohammed (Tanjungpura Journal of Coaching Research, 2025)
Background. The implementation of Video Assistant Referee (VAR) technology represents one of the most significant administrative innovations in modern football management, particularly in leagues with pre-existing governance challenges. The Iraq Stars League introduced VAR in the 2024-2025 season, creating an opportunity to examine its impact on perceived refereeing fairness. This study aims to evaluate the effective management of VAR technology implementation and its impact on refereeing governance in the Iraq Stars League, with particular focus on the perceptions of Kurdistan Region clubs' supporters. Methods. Using an administrative survey methodology, this research analyzed data from 200 participants supporting three Kurdistan Region clubs (Duhok, Zakho, and Erbil). The study employed a quantitative approach with a validated instrument measuring technology knowledge, management transparency, perceived bias, and satisfaction with technology impact. Results. Data revealed significant differences in perceptions between fan bases, with Zakho supporters expressing the lowest satisfaction levels regarding VAR transparency. Statistical analysis documented substantial historical governance challenges affecting Kurdistan Region clubs and indicated only moderate improvement in perceived refereeing fairness following VAR introduction. While all stakeholder groups reported significant improvements in perceived administrative fairness after VAR implementation, these ratings still remained below neutral, indicating persistent concerns. Conclusion. The findings highlight that while VAR improves perceptions of refereeing fairness, it cannot resolve underlying governance issues in regions with existing tensions. The study offers recommendations to enhance transparency in developing football league management.